Small Region, Big Impact: Highly Anisotropic Lyman-continuum Escape from a Compact Starburst Region with Extreme Physical Properties - Kim, Keunho J.; Bayliss, Matthew B.; Rigby, Jane R.; Gladders, Michael D.; Chisholm, John; Sharon, Keren; Dahle, Håkon; Rivera-Thorsen, T. Emil; Florian, Michael K.; Khullar, Gourav; Mahler, Guillaume; Mainali, Ramesh; et al. (The Astrophysical Journal Letters, 2023)
Extreme, young stellar populations are considered to be the primary contributor to cosmic reionization. How the Lyman continuum (LyC) escapes these galaxies remains highly elusive, and it is challenging to observe this process in actual LyC emitters without resolving the relevant physical scales. We investigate the Sunburst Arc, a strongly lensed LyC emitter at z = 2.37 that reveals an exceptionally small-scale (tens of parsecs) region of high LyC escape. The small (<100 pc) LyC-leaking region has extreme properties: a very blue UV slope (β = −2.9 ± 0.1), a high ionization state ([O iii] λ5007/[O ii] λ3727 = 11 ± 3 and [O iii] λ5007/Hβ = 6.8 ± 0.4), strong oxygen emission (EW([O iii]) = 1095 ± 40 Å), and a high Lyα escape fraction (0.3 ± 0.03), none of which are found in nonleaking regions of the galaxy. The leaking region's UV slope is consistent with approximately "pure" stellar light that is minimally contaminated by the surrounding nebular continuum emission or extinguished by dust. These results suggest a highly anisotropic LyC escape process such that LyC is produced and escapes from a small, extreme starburst region where the stellar feedback from an ionizing star cluster creates one or more "pencil-beam" channels in the surrounding gas through which LyC can directly escape. Such anisotropic escape processes imply that random sight-line effects drive the significant scatters between measurements of galaxy properties and LyC escape fraction, and that strong lensing is a critical tool for resolving the processes that regulate the ionizing budget of galaxies for reionization.
Keywords: Space and Planetary Science; Astronomy and Astrophysics